Factors Associated with Dental Caries in Children Aged 4-6 Years Old - Nur Widayati (Universitas Airlangga, 2014)
Dental caries is one of the dental health problems. Impact, teeth become brittle, hollow, even broken. Dental caries experiences a loss of power to make a child chewing and digestive disruption, which resulted in a growth of less than the maximum. This study aims to determine the relationship of parents’ behavior towards the maintenance of dental health of children (feeding habits sweet, sticky and drinking milk, teeth maintenance, inspection tooth, and mouth) with dental caries in the Kindergarten (TK) of R.A Bustanussholihin in Balun village Turi District of Lamongan. This study Analytics whose data is collected with a cross-sectional sample of kindergarten children aged 4–6 years with a total sample of 49 children. The collection of primary data through interviews parents kindergarten of R.A Bustanussholihin student using questionnaires and secondary data obtained from the agency are in the region of the profile data kindergarten of R.A Bustanussholihin in Balun Village of Turi District of Lamongan. This study used a correlation coefficient of contingency. Based on the results of the contingency coefficient correlation test showed that the factors that have a strong relationship are the habit of feeding the sweet, sticky, and drink milk with a value of P = 0.504. While the factors that have a weak link in the habit of maintaining dental hygiene habits of children and child oral examination. From this study, it can be concluded that there is a relationship or a strong correlation between feeding habits sweet, sticky, and drinking milk with the incidence of dental caries in children aged 4–6. So as to prevent dental caries severity we need to hold counseling on feeding sweet, soft, and gooey on the effect of dental caries as well as how it should be formula feeding or breast